Research Methods in Deliberative Democracy - Ercan, Selen A.; Asenbaum, Hans; Curato, Nicole; Mendonça, Ricardo F. (Oxford University Press, 2022)
Research Methods in Deliberative Democracy is the first book that brings together a wide range of methods used in the study of deliberative democracy. It offers thirty-one different methods that scholars use for theorizing, measuring, exploring, or applying deliberative democracy. Each chapter presents one method by explaining its utility in deliberative democracy research and providing guidance on its application by drawing on examples from previous studies. The book hopes to inspire scholars to undertake methodologically robust, intellectually creative, and politically relevant research. It fills a significant gap in a rapidly growing field of research by assembling diverse methods and thereby expanding the range of methodological choices available to students, scholars, and practitioners of deliberative democracy.